2019
DOI: 10.1002/mus.26486
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of RNA sequencing to resolve unusual GNE myopathy with a novel promoter deletion

Abstract: Introduction: UDP N‐acetylglucosamine2‐epimerase/N‐acetylmannosamine‐kinase (GNE) gene mutations can cause mostly autosomal‐recessive myopathy with juvenile‐onset known as hereditary inclusion‐body myopathy (HIBM). Methods: We describe a family of a patient showing an unusual HIBM with both vacuolar myopathy and myositis without quadriceps‐sparing, hindering diagnosis. We show how genetic testing with functional assays, clinical transcriptome sequencing (RNA‐seq) in particular, helped facilitate both the diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…To date, >250 genes are associated with various inherited neuromuscular disorders (NMDs) ( 1 4 ) comprising a broad heterogeneous group of genetic myopathies. However, significant numbers of affected patients remain without a definitive molecular diagnosis due to novel gene or multiple gene associations with disease ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…To date, >250 genes are associated with various inherited neuromuscular disorders (NMDs) ( 1 4 ) comprising a broad heterogeneous group of genetic myopathies. However, significant numbers of affected patients remain without a definitive molecular diagnosis due to novel gene or multiple gene associations with disease ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…The current diagnostic pathway for Dysferlinopathy typically only assesses Dysferlin protein expression and DYSF DNA-sequencing [35], but here we show that by using a tiered analytical approach we can tease apart all possible aberrations at RNA-transcript structural-, exonic-, allelic-, gene-, and protein-expression levels that will lead to not only a higher diagnostic yield but also important help enable patient stratification by connecting molecular underpinnings to clinical severities. One limitation of this study is that the prior DNA-testing were done non-uniformly (Exome/Gene-Panel/Sanger) based on respective physician discretion, outcome measurements, as well as novel therapy discoveries [10,24].…”
Section: Discussionmentioning
confidence: 99%
“…We reasoned that whole-blood targeted-RNA-Seq of 274 NMD-associated genes expressed in skeletal muscle (Table S1) [24] with high read-depth in a tiered-analysis (Tiers1/2/3; DYSF isoform-expression differences between blood and muscle are unlikely to hinder analysis since alternate exons are in-frame and well-expressed in blood except for exon 17 (Table 3 of [25]). 51 Dysferlinopathy-suspected patients who provided consents underwent RNA-Seq, among whom 38 patients' %DYSF and/or DNA-sequencing were unable to provide a complete molecular diagnosis and in 13 patients the pathomechanism of the identified DYSF-variants were unclear.…”
Section: Combinatorial Biomarker Approach Enhances Genotype-phenotypementioning
confidence: 99%
“…Recently, Chakravorty et al reported that a patient with a deletion in the promoter of one allele GNE and having a single mutation in the other allele showed GNE myopathy phenotype 6 . This shows that heterozygous knockout or non-functional one allele may lead to GNE Myopathy.…”
Section: Characterization Of Gne Exon-3 Knockout Cell Line (Skm-gnehz)mentioning
confidence: 99%
“…Both homozygous and compound heterozygous mutations have been reported in patients with predominantly M743T in Persian Jews, A207V in Japanese, I618T in Roma Gypsies and V727M in Indian subcontinent [1][2][3][4][5] . A patient with deletion in promoter region of one allele and single mutation in other allele has also been reported with GNE Myopathy 6 . Though it is a slowly progressive disease, progressivity also depends on the nature of biallelic mutation 7 .…”
mentioning
confidence: 99%